A diversidade sexual e de gênero nos currículos que (in)formam pedagogas(os), professores(as) de Educação Física e bacharéis em Direito na Universidade de Brasília (UnB) - Santos, Anderson Neves dos (Universidade Federal do Tocantins, 2021)
This research is linked to the Research Line Curriculum, Teacher training and teaching knowledge of the Education Graduating Program of the Federal University of Tocantins (PPGE/UFT), in association with the Study and Research Group on Curriculum and Educational Policies (Gepce). The study approaches the thematic sexual and gender diversity in the perspective of the post-critical curriculum and its problematic is delimited by the question: What is the (re)presentation of sexual and gender diversity in curriculum of under graduation courses of Pedagogy, Physical Education and Law of the University of Brasília (UnB). The investigation implied qualitative approach in ethnomethodology and critical ethno-research perspective, and in the ethno-research training, using bibliographical research and ethno-texts in documental research of curriculum of under graduation courses. Based on the methodology, six ethno-texts were studied, two of each course, investigated with descriptive-interpretive type of content analysis. From the analysis, four sub supportive notions were grouped: 1) “Presence-absence” of sexual and gender diversity in curriculum of courses; 2) (In)visibility of sexual and gender identities and a curriculum heteronormativity; 3) Training insufficiencies for teachers and supervised silenced by official documents; and 4) Disarticulation between teacher training and public policies in work effectiveness with/for sexual and gender diversity. Final considerations shows that curriculum which inform/train teachers and lawright operators (including the human rights) are omitted in education for sexual and gender diversity. More researches in education approaching formative curriculum are necessary, because they are still designed/planned/practiced in its male and heteronormative meaning.